Internal and External Evaluation of the Book Principles and Methodology of Translation Published by SAMT - Alireza Rasti (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The present research aimed at analyzing the book Principles and Methodology of Translation in terms of its formal characteristics, content, and methodology, using the critical library research method in general and McDonough, Shaw, and Masuhara’s (2013) textbook evaluative framework in particular. The findings showed that, despite the groundbreaking nature of the book, in terms of the methodology, the book does not adhere to any one linguistic theory in a systematic way, and that it presents some concepts in a rather food-recipe fashion. Content-wise, the book does not offer any big picture of the science and practice of translation, its domain, and history. Some suggestions are finally made in an attempt to enhance the quality of the book.